Thermal Behaviour of Paraffin Wax/Poly Vinyl Alcohol Composite Material - ALubaidi, Aseel Basim; Abas, Falak O.; Abass, Raghad A.; Abdulredhi, Nazar J. (Al-Khwarizmi Engineering Journal, 2017)
Polymer additives binder system provides many properties useful in thermal energy storage (TES) then developed the efficient energy storage materials and green strength bodies system.This paper studies the thermal energy storage property for polyvinyl alcohol (PVOH) / paraffin wax (WPw) blends. To enhance paraffin wax thermal conductivity, PVOH as a material which high conductivity was employed. A fixed weight of Paraffin wax was dispersed with PVOH heterogeneously at different additive weights ratios of PVOH/Pw (50/50, 67/33, 75/25, and 80/20) wt. ratio respectively. The composite material was prepared using wetted pressing method.Both base materials (polyvinyl alcohol and paraffin wax) were scanned using differential scanning calorimeter (DSC) under non-isothermal conditions, the result was analysed to determine the thermal transition temperature of PVOH and paraffin wax base material. The thermal decomposition of PVOH and waste paraffin wax proved that high transition temperature (TG) for PVOH reached 209ᴼc rather than wax of 60ᴼc respectively. This result shows that PVOH suppress the thermal stability of PVOH/waste paraffin wax composites. Afterward examines the thermal conductivity enhancement using Lee- disk techniques. Composite materials PVOH/paraffin wax have a high thermal conductivity which increases thermal conductivity of waste paraffin wax as a heat storage media and  this allows to apply change in phase with wide range of temperatures, and the highest decreased ratio of phase-change heat is very low, compared to that of paraffin only. Therefore, PVOH, added to paraffin which has significant potential for enhancing the thermal storage characteristics of paraffin.A wax/PVOH system acts as strength body resistance to sever contact of both air and moisture then a moisture absorbance percent was achieved by use both Fourier transform infrared spectroscopy (FTIR) techniques and moisture solutions (100% H2O) for all pure and composite material system Pw/PVOH, the results shows high resistance to ambient conditions (air/ moisture) for composite system rather than pure materials (PVOH and Pw).